STUDI EKSPERIMENTAL PENGARUH PROSES PEMBAKARAN TERHADAP SIFAT MEKANIS PADA BAJA TULANGAN - Ella Sundari; Taufikurrahman .; Sepri Alfarizi (Jurnal Turbulen, 2019)
Reinforcing steel is a very important material contained in the concrete, where it has a function as a tensile load receiver where the concrete is very weak in receiving the tensile load. In the event of concrete and reinforced concrete fires can be complementary because the reinforcing steel can accept tensile load while the concrete can accept the press load. The method of testing conducted in this study using the method of tensile testing, metallography, and composition testing. Where prior to testing the reinforcing steel is first casted in the concrete after it is done combustion process with a temperature of 400 ° C, 600 ° C, 800 ° C and cooled with water and air cooling medium. After done all the testing process got result that is reinforcing steel which has the most optimal tensile stress occurred at temperature of 600 ° C with water cooling media which got value of tensile strength equal to 596,46 N / mm2. Keywords: : Reinforcing Steel, Tensile Test